Identification of a Dominant Chlorosis Phenotype Through a Forward Screen of the Triticum turgidum cv. Kronos TILLING Population - Harrington, Sophie A.; Cobo, Nicolas; Karafiátová, Miroslava; Doležel, Jaroslav; Borrill, Philippa; Uauy, Cristobal (Frontiers in Plant Science, 2019)
Durum wheat (Triticum turgidum) derives from a hybridization event approximately 400,000 years ago which led to the creation of an allotetraploid genome. The evolutionary recent origin of durum wheat means that its genome has not yet been fully diploidised. As a result, many of the genes present in the durum genome act in a redundant fashion, where loss-of-function mutations must be present in both gene copies to observe a phenotypic effect. Here we use a novel set of induced variation within the cv. Kronos TILLING population to identify a locus controlling a dominant, environmentally-dependent chlorosis phenotype. We carried out a forward screen of the sequenced cv. Kronos TILLING lines for senescence phenotypes and identified a line with a dominant early senescence and chlorosis phenotype. Mutant plants contained less chlorophyll throughout their development and displayed premature flag leaf senescence. A segregating population was classified into discrete phenotypic groups and subjected to bulked-segregant analysis using exome capture followed by next-generation sequencing. This allowed the identification of a single region on chromosome 3A, Yellow Early Senescence 1 (YES-1), which was associated with the mutant phenotype. While this phenotype was consistent across four years of field trials in the UK, the mutant phenotype was not observed when grown in Davis, CA (US). To obtain further SNPs for fine-mapping, we isolated chromosome 3A using flow sorting and sequenced the entire chromosome. By mapping these reads against both the cv. Chinese Spring reference sequence and the cv. Kronos assembly, we could identify high-quality, novel EMS-induced SNPs in non-coding regions within YES-1 that were previously missed in the exome capture data. This allowed us to fine-map YES-1 to 4.3 Mb, containing 59 genes. Our study shows that populations containing induced variation can be sources of novel dominant variation in polyploid crop species, highlighting their importance in future genetic screens. We also demonstrate the value of using cultivar-specific genome assemblies alongside the gold-standard reference genomes particularly when working with non-coding regions of the genome. Further fine-mapping of the YES-1 locus will be pursued to identify the causal SNP underpinning this dominant, environmentally dependent phenotype.